2009
DOI: 10.1007/s00520-009-0577-7
|View full text |Cite
|
Sign up to set email alerts
|

Symptom clusters in patients with advanced cancers

Abstract: In patients with advanced cancers, distinct symptom clusters can be identified, which are influenced by primary cancer site. Treatments directed at symptom clusters rather than individual symptoms may provide greater therapeutic benefit. Further prospective studies are warranted in order to develop more effective targeted palliative interventions for the advanced cancer patient population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
114
4
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 142 publications
(140 citation statements)
references
References 41 publications
17
114
4
5
Order By: Relevance
“…Comparing our results to studies that specifically report ESAS scores from a palliative care unit or clinic, 26,27,[31][32][33][34][35][36][37][38] the symptom prevalence and symptom scores from these palliative patients are consistently higher than in our study. For example, in a study of 1296 patients attending a palliative radiation oncology outpatient clinic, 26 the median symptom score was 5 for fatigue, 2 for dyspnea, 3 for pain, and 2 for depression compared with our results of 3, 0, 1, and 0, respectively.…”
Section: Sarcomasupporting
confidence: 56%
See 1 more Smart Citation
“…Comparing our results to studies that specifically report ESAS scores from a palliative care unit or clinic, 26,27,[31][32][33][34][35][36][37][38] the symptom prevalence and symptom scores from these palliative patients are consistently higher than in our study. For example, in a study of 1296 patients attending a palliative radiation oncology outpatient clinic, 26 the median symptom score was 5 for fatigue, 2 for dyspnea, 3 for pain, and 2 for depression compared with our results of 3, 0, 1, and 0, respectively.…”
Section: Sarcomasupporting
confidence: 56%
“…Moreover, the prevalence of fatigue and depression in our cohort is consistent with other reports. [26][27][28][29][30] The high prevalence of these symptoms represents areas for continued research and treatment to improve symptom management. Furthermore these results are important to practitioners because they focus on a defined ambulatory population, are population-based, and originate from validated symptom assessment tools.…”
Section: (0)mentioning
confidence: 99%
“…PCA is statistical technique used in prior studies in patients with advanced cancer to examine the symptoms that correlate with each other to form a distinct and stable pattern, which is known as a component in the PCA model [45][46][47][48]. In 114 evaluable patients, the following three clusters accounted for 63% of the total variance: the fatigue/anorexia-cachexia/depression (FAD) cluster, the sleep/ anxiety/drowsiness (SAD) cluster, and the pain/dyspnea (PD)…”
Section: Resultsmentioning
confidence: 99%
“…[34][35][36][37][38][39][40][41] According to two analyses of patients with terminal cancer in varied palliative care settings, fatigue was the most frequently reported symptom, and pain, depression, and anxiety were the most distressing symptoms. 2,42 In this study, the most frequently reported symptoms were pain (58%), dyspnea (52%), constipation (45%), and fatigue (23%).…”
Section: Discussionmentioning
confidence: 99%